Particle size and roasting on water sorption in conilon coffee during storage - Corrêa, Paulo Cesar (2016)
The aim of this work was to evaluate alterations on the water sorption of coffee due to the effect of roast, grind and storage in two temperatures (10 and 30 ºC) during 180 days. Crude grain coffee (Coffea canephora) with average initial moisture content of 12.61 % (d.b.) was used. Grain was roasted at two levels: medium light (ML) and moderately dark (MD). Afterwards, grain was processed in three different particle sizes: fine (0.59 mm), medium (0.84 mm) and coarse (1.19 mm), besides the whole coffee lot. Samples prepared were then stored in two temperatures (10 and 30 ºC). These were analyzed during six months, at five distinct times (0, 30, 60, 120 and 180 days) regarding moisture content and water activity. Furthermore, mathematical modeling and thermodynamic properties acquisition of the coffee moisture adsorption process were accomplished. A split plot design was used, in which plots consisted of storage period and split-plots consisted of a 2 x 4 x 2 factorial (two roasting degrees, four particle sizes and two storage temperatures), with five repetitions.It was concluded thatparticle size did not significantly affectedmoisture content of coffee, independently of roast degree; Sigma-Copace model best represented hygroscopic equilibrium for sorption of roasted coffee; with moisture content reduction, an increase of differential enthalpy and entropy of sorption and Gibbs free energy occurs.